Análise de estruturas reticuladas utilizando o software excel pelo método dos elementos finitos - Suzuki, Marcos Seiti [UNESP] (2014)
The use of the finite element method is well diffused through commercial software, but the mathematical procedure often goes unnoticed by users. The software uses the method in the analysis of solid structures, heat transfer fluids and electromagnetism. Such software is expensive frequently not accessible to students or professionals. For people who want to do an analysis of structural elements such as truss and frames to purchase this kind of software is uneconomical. This work developed a routine in Visual Basic for Aplication of Micrsoft Excel using the finite element method, able to do analysis in space trusses, plane beams and plane frames, turning accessible one who want analyze such structures or those who want to know well the method. The Microsoft Excel has features matrix operations and various mathematical operations and any other operation or manipulation of data required it has programming in Visual Basic for Aplication. Excel is being on most computers with Microsoft Windows operating system enables what its portability between computers without bigger difficulties. For this a review of the finite element method and Excel features have been realized. Validation of results was done by comparing results obtained in ANSYS software